Measuring The Interest of Travellers Staying at Larose Villa and Suites Camp Canggu in Batu Bolong Canggu Bali - I Gusti Ayu Ninik Anggreni; I Nengah Subadra; Ni Nyoman Ardani (Tourism and Hospitality Insights, 2026)
Introduction: Bali is one of the leading tourist destinations with rapid growth in the accommodation sector, creating intense competition among lodging providers, including Larose Villa and Suites Camp Canggu, which has experienced fluctuations in occupancy rates. This study aims to analyze the effect of facilities and pricing on tourists’ interest in staying at the villa. Methods: This research employed a quantitative descriptive approach with a sample of 100 respondents selected through non-probability sampling, consisting of guests who had stayed at the villa. Data were collected using questionnaires and analyzed using descriptive statistics and multiple linear regression analysis. Results: The results show that facilities have a positive and significant effect on tourist interest (t = 5.969; p < 0.05), and pricing also has a positive and significant effect (t = 5.301; p < 0.05). Simultaneously, facilities and pricing significantly influence tourist interest (F = 66.922; p < 0.05), with a coefficient of determination of 57.1%. Conclusion: Improving facility quality and implementing competitive pricing strategies are essential to increase tourists’ intention to stay and enhance occupancy rates.